Reproductive populations of the Critically Endangered bat Phyllonycteris aphylla at two new locations in Jamaica - Phillip J. Oelbaum; Ronald P. Hall; Damion L. Whyte; Ronald S. Stewart; Jan Pauel; Silvia Kouwenberg; Elizabeth R. Dumont; Kenneth C. Welch (Oryx)
The Jamaican flower bat Phyllonycteris aphylla is categorized as Critically Endangered on the IUCN Red List. It is endemic to Jamaica and formerly known only from Stony Hill Cave, where there are an estimated c. 500 individuals. Previously declared extinct twice, its rediscovery in 2010 at Stony Hill Cave marked new hope for the conservation of this important species. Although little is known about its ecology, the species is presumed to be a cave-obligate rooster and to rely exclusively on so-called hot caves, which are defined by high ambient temperatures and low air quality. In March–April 2023, we surveyed bats at seven caves throughout Jamaica. At two of these, Green Grotto Caves, St. Ann, and Rock Spring Caverns, St. Mary, we captured both male and pregnant female P. aphylla. At Green Grotto Caves, we captured 24 P. aphylla, and 66 at Rock Spring Caverns. We believe Rock Spring Caverns to be one of the largest known roosts of P. aphylla. Neither of these sites are hot caves as both are moderated by flowing water, although warmer chambers may be more important to this bat than to other species. Further monitoring of these populations and continued exploration of other potential roosts are vital for the protection of this species.